Functionalized monolithic columns: Recent advancements and their applications for high-efficiency separation and enrichment in food and medicine - Si, Helong; Wang, Quan; Guo, Yuanyuan; Zhao, Yuxin; Li, Hongya; Li, Shuna; Wang, Shuxiang; Zhu, Baocheng (Frontiers in Chemistry, 2022)
The chromatographic column is the core of a high-performance liquid chromatography (HPLC) system, and must have excellent separation efficiency and selectivity. Therefore, functional modification materials for monolithic columns have been rapidly developed. This study is a systematic review of the recently reported functionalized monolithic columns. In particular, the study reviews the types of functional monomers under different modification conditions, as well as the separation and detection techniques combined with chromatography, and their development prospects. In addition, the applications of functionalized monolithic columns in food analysis, biomedicine, and the analysis of active ingredient of Chinese herbal medicines in recent years are also discussed. Also reviewed are the functionalized monolithic columns for qualitative and quantitative analysis.It provided a reference for further development and application of organic polymer monolithic columns.